2022
DOI: 10.1097/md.0000000000031502
|View full text |Cite
|
Sign up to set email alerts
|

Value of CT spectral imaging in the differential diagnosis of sarcoidosis and Hodgkin’s lymphoma based on mediastinal enlarged lymph node: A STARD compliant article

Abstract: To investigate the imaging characteristics of sarcoidosis and Hodgkin's lymphoma based on mediastinal enlarged lymph node using spectral CT and evaluate whether the quantitative information can improve the differential diagnosis of these diseases. This retrospective study was approved by the institutional review board, and written informed consent was obtained from all patients. Overall, 21 patients with sarcoidosis and 39 patients with Hodgkin's lymphoma were examined with CT spectral imaging during the arter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Wang Ren et al also suggested the same conclusion: lymph nodes in patients with pulmonary sarcoidosis showed roughly uniform enhancement after enhanced scanning, while the enhancement of lung cancer lymph nodes was not obvious. Also, in that study, tuberculous lymph nodes showed circular enhancement, and lymph nodes affected by lymphoma showed slight enhancement [ 16 ]. However, there was no obvious statistical significance in the difference in enhancement degree grading ( p = 0.242), which could not be excluded due to the small sample size.…”
Section: Diagnostic Value Of Imaging In Pulmonary Sarcoidosismentioning
confidence: 98%
See 1 more Smart Citation
“…Wang Ren et al also suggested the same conclusion: lymph nodes in patients with pulmonary sarcoidosis showed roughly uniform enhancement after enhanced scanning, while the enhancement of lung cancer lymph nodes was not obvious. Also, in that study, tuberculous lymph nodes showed circular enhancement, and lymph nodes affected by lymphoma showed slight enhancement [ 16 ]. However, there was no obvious statistical significance in the difference in enhancement degree grading ( p = 0.242), which could not be excluded due to the small sample size.…”
Section: Diagnostic Value Of Imaging In Pulmonary Sarcoidosismentioning
confidence: 98%
“…In a retrospective analysis of the diagnostic value of 64-slice spiral CT-enhanced scanning in pulmonary sarcoidosis, Tian Bin showed that 30 patients had obvious enhanced characteristics of enlarged lymph nodes, and the CT value increased by 32–43 HU after enhancement, with uniform lymph node density and clear boundaries without fusion. Also, intrapulmonary nodules were mostly seen in the middle and upper lungs, mostly distributed along the bronchovascular bundle, and reticular nodules with irregular shapes of 2–5 mm were the most common type of nodules [ 16 ]. These enhanced lymph node characteristics were basically the same as those in the study of He Yu et al [ 17 ].…”
Section: Diagnostic Value Of Imaging In Pulmonary Sarcoidosismentioning
confidence: 99%
“…In recent years, the commonly used imaging techniques include ultrasound, computed tomography imaging, emission computed tomography imaging, magnetic resonance imaging (MRI), and X-ray, but they are not widely used due to their inherent limitations. [8,9] With the development of neuroimaging technology, the emergence of functional MRI (fMRI) has provided a more effective means of studying the mechanisms of acupuncture in the treatment of gynecological diseases. fMRI not only provides real-time imaging of the brain but also has the advantage of noninvasive, high-quality imaging with high spatial resolution compared to other techniques.…”
Section: Introductionmentioning
confidence: 99%